Constructing Problems by Promoting Solutions: Corporate Advertisements about U.S. Poverty. - Silver, Ira; Boyle, Mary-Ellen (Journal of Poverty)
During the 1980s and 1990s corporations publicized their “social responsibilities” in popular print media. These ads make claims about issues such as the environment, consumer protection, neighborhood revitalization, education, arts and entertainment, and health. We examine a set of these ads and analyze the ways in which they construct social problems. We focus on ads about poverty, assessing the meaning and impact of business discourse about poor people and economic inequality. In showing that ads typically construct poverty by promoting quick-fix solutions for particular individuals, we argue that corporations play a unique role in obfuscating the structural causes of poverty and in shaping our understanding of the problem more broadly. As a new channel for claims making, such corporate ads complement and contradict the messages of other media, uniquely establishing corporate authority and influencing public discourse.